Analisis Dampak Video 'For Your Page' Tiktok Terhadap Penyebaran Informasi Palsu Atau Fitnah Tentang Agama Islam: Tantangan Dan Solusi - Azzahra, Audree; Azzuri, Denisa Panseria; Rasyid, Erlinda Alya; Humayra, Zahra Siti; Parhan, Muhamad (Peneliti.net, 2024)
This research focuses on analyzing the impact of TikTok's 'For Your Page' videos on the spread of false or slanderous information about Islam. Using quantitative research methods, questionnaires will be distributed to TikTok users to evaluate their perceptions of content that may lead to the spread of false or harmful information about Islam. Through analysis of the data collected, this research aims to understand the extent to which TikTok videos influence people's views on Islam and identify potential risks of spreading false information. The research will also explore the challenges faced in dealing with this phenomenon. By focusing on factors such as content ranking algorithms and the lack of effective filter mechanisms, this research will provide insight into the constraints that can amplify the spread of false information.